PENULIS ATAU AMANUENSIS SURAT IBRANI? - Nggadas, Deky Hidnas Yan (STT Amanat Agung, 2023)
The consensus of NT scholarship on Origen's agnosticism for the identity of the writer of the Epistle to the Hebrews is exactly wrong. Origen, explicitly and repeatedly quotes from the Epistle to the Hebrews as the writing of the Apostle Paul. The writer proposes that Origen's agnostic statement is not related to the identity of the author of the Letter to the Hebrews but his amanuensis.